Screening and Identification of Latilactobacillus curvatus Z12 From Rumen Fluid of an Adult Female Sika Deer as a Potential Probiotic for Feed Additives - Zhang, Yan; Liang, Shuang; Zhao, Meng Di; Yang, Xue; Choi, Seong Ho; Li, Guang Yu (Frontiers in Veterinary Science, 2021)
Lactic acid bacteria (LAB) are the main microorganisms used as probiotics against gastrointestinal inflammation. The objective of this study was to evaluate the potential probiotic characteristics (antimicrobial activity, artificial gastrointestinal model resistance, cell surface hydrophobicity, and autoaggregation ability) and safety characteristics (hemolytic activity, antimicrobial resistance, and in vivo safety) of LAB isolated from the rumen fluid of an adult female sika deer. Two isolated strains identified as Latilactobacillus curvatus Z12 and Z19 showed good antimicrobial activity against enteropathogenic Escherichia coli (ATCC25922), Salmonella typhi (ATCC14028), and Staphylococcus aureus (ATCC25923). In addition, L. curvatus Z12 exhibited higher artificial gastrointestinal model resistance, cell surface hydrophobicity and autoaggregation ability than L. curvatus Z19. Therefore, regarding safety characteristics, only L. curvatus Z12 was evaluated. Upon assessment of safety, L. curvatus Z12 was negative for hemolytic activity and susceptible to penicillin G and cefamandole. Furthermore, an in vivo safety assessment showed that high-dose L. curvatus Z12 (109 CFU/mL) supplementation not only had no adverse effects on body weight gain, feed intake, and organ coefficients of treated mice but also played a key role in promoting the immune system maturation of treated mice. This research revealed that L. curvatus Z12 possesses desirable probiotic characteristics and could be used as a potential probiotic feed additive to improve sika deer health.